2020
DOI: 10.1557/jmr.2019.392
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ceramic particle size on densification behavior, microstructure formation, and performance of TiB2-reinforced Al-based composites prepared by selective laser melting

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…1c [39]. Intuitively, micrometric particles altered the molten pool rheology, surface tension, and metal vapor density, as has been reported [7,40,41]. Also, a pronounced spattering phenomenon was observed when 5 vol.% coated -D was mixed with Cu compared to a pure Cu bed situation (Fig.…”
Section: Conventional Laser Powder Bed Fusion Of Cu/d Compositessupporting
confidence: 64%
See 1 more Smart Citation
“…1c [39]. Intuitively, micrometric particles altered the molten pool rheology, surface tension, and metal vapor density, as has been reported [7,40,41]. Also, a pronounced spattering phenomenon was observed when 5 vol.% coated -D was mixed with Cu compared to a pure Cu bed situation (Fig.…”
Section: Conventional Laser Powder Bed Fusion Of Cu/d Compositessupporting
confidence: 64%
“…The difficulties encountered in the 3D printing of micro composites arise from the significant size of the solid reinforcement, which plays a critical role in the densification behavior. L. Xi et al showed that finer reinforcements allow manufacturing denser composites compared to a coarser reinforcement [7]. Micrometric particles significantly alter the transit molten pool dynamics, rheology, and flowability, leading to porous parts' formation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Metal vapor-induced entrainment caused powder-spattering behavior [ 44 ]. To be intuitive, micrometric particles changed the surface tension, molten pool rheology, and metal vapor density according to declaration [ 45 , 46 , 47 ]. Also, it was believed that the imbalance of the molten pool, hot spatter collision during flight and entrained particles gathered on the solidified area were among the major driving forces for big spatter production.…”
Section: Resultsmentioning
confidence: 99%